Manufacturing exports determinants across Mexican states, 2007-2015 - René Cabral Torres; Jorge Alberto Alvarado (Banco de México, 2019)
This article examines manufacturing export determinants across Mexican states and regions from 2007 to 2015, paying particular attention to the role of FDI. The analysis considers internal and external determinants of manufacturing exports under static and dynamic panel data methods, obtaining three main results. First, the ratio of manufacturing to total GDP is the most consistent determinant explaining exports performance, regardless of the econometric specification employed. Second, static panel data estimations under GMM techniques suggest different sensitivity to FDI across regions, with the Mexico-U.S. border region observing the strongest short-term effect of FDI on manufacturing exports. Finally, using dynamic panel data methods, we observe a significant persistence and similar long-term effects of FDI across most of the regions on the exporting manufacturing sector.
Keywords: F16; F36; 330; Exports; Foreign Direct Investment; Panel Data; Mexico